Analytical study on seepage field of subsea twin tunnels constructed by NATM. (15th November 2022) - Qin, Zhenggui; He, Weiguo; Zhou, Huagui
Abstract: When two tunnels are close to each other, there will be serious mutual interference in the seepage fields. It may result in errors of more than 30% to use an independent single-hole tunnel model for seepage field analysis. An analytical model for the seepage field of subsea twin tunnels is proposed, and an analytical solution of the seepage field is obtained based on the superposition principle. The analytical solution is verified by degradation analysis, a numerical test and an engineering case. It is shown that: (1) The optimal net distance of twin tunnels is 1 times the tunnel diameter. At this time, the water inflow into one of the twin tunnels is the lowest, which is about 70% of the water inflow into the independent single-hole tunnel. (2) When the diameter of the drainage tunnel is reduced by 75% (the excavation area is reduced by 94%, and the project cost is greatly reduced), the water inflow into the main tunnel increases by only 18%. Therefore, small diameter drainage tunnel is the priority strategy. (3) The drainage tunnel should preferably be arranged at 45° obliquely below the main tunnel. Highlights: The analytical soulution of seepagefield of twin tunnels is obtained. The seepage fields exhibit serious mutual interference in twin tunnels at a close distance. The reasonable clear distance of twin tunnels is 1–2 times the tunnel diameter. Small-sized drainage tunnel is preferred, such as 0.5 times the diameter of the main tunnel. The discharge tunnel should be arranged at 45° obliquely below the main tunnel.